INCIDENCE OF INFECTION FOR LEPTOSPIRA SPP. IN CAPYBARAS (HYDROCHOERUS HYDROCHAERIS) REARED IN CAPTIVITY IN IQUITOS - Cueva A., Esther (2010)
The objective of this study was to determine the incidence of Leptospira sp., in capybaras (Hydrochoerus hydrochaeris) from a zoo farm in Iquitos, Loreto, Peru. Blood samples from 36 young and adults capyrabas, both female and male, were collected in three samplings periods with a 2-month interval for detecting antibodies against 13 serovars of Leptospira sp. by microaglutination test. The 97.2, 100 y 100% of the samples collected during the first, second and third sampling period had antibodies against Leptospira sp. respectively. The serovar georgia, canicola and ballum were detected in the first, second and third sample, pomona and australis in the second and third, and tarassovi only in the third sampling period. The most frequent serovars were georgia, canicola, and ballum. The accumulated incidence of Leptospira sp. infection was 86.0 ± 18.2% (31/36) animals/0.25year. The accumulated incidence of each serovar also indicated that georgia (100%), ballum (36.3%), canicola (25.8%) and tarassovi (16.6%) were the more frequent. The samples resulted negative to antibodies against the serovars icterohemorrhagiae, wolffi, hardjo, bratislava, grippotyphosa and javanica. The results indicate that Leptospira sp. infection is endemic on the capyraba population in the zoo farm in Iquitos city.